Replacing Provocation in England and Wales: Examining the Partial Defence of Loss of Control. (13th May 2013) - Fitz‐Gibbon, Kate
<x xml:space="preserve">Abstract</x> In October 2010, provocation was abolished as a partial defence to murder in England and Wales. Through the introduction of the Coroners and Justice Act 2009, a new partial defence of loss of control was implemented. This sought to overcome problems associated with the provocaton defence and the gendered operation of the law of homicide, particularly in relation to male‐perpetrated intimate homicides, and the inadequate response of the law to the contexts in which battered women kill. This article first provides an account of these developments, and then examines legal stakeholders' perceptions of them. Drawing from in‐depth interviews with criminal justice professionals, it considers their perceptions of the operation of the law of homicide during a period of transition, specifically considering the formulation of the new partial defence, the initial effects of its implementation, and the significant differences between the Law Commission's recommendations and the reforms implemented by the government.